Itinerante Futebol Clube: a desconstrução do torcer e as relações entre os clubes e as torcidas - Alexandre Francisco Alves (2015)
The purpose of this study was to understand the process of (un) configuration and (re) configuration of the supporting in the two cities, Betim-MG and Ipatinga-MG, and how they established the relationship of the fans with the Ipatinga FC / EC Betim. We tried to understand how the fans reacted to these territorial changes, caused tensions and the possible consequences in the scenario where a club settled and othersceased to exist and to set the supporting in the cities, and how was the process of ( re) appropriation and (mis) appropriation of the club by fans. In addition, we sought to investigate the reasons for this (s) club (s) to change name, shield, ie its identity and its headquarters. In the city of Ipatinga were applied 108 forms together with the Ipatinga FC fans. In the city of Betim, they were interviewed six fans Betim EC that accompanied the team during the time he was in town. The managers of the municipalities of Ipatinga-MG and Betim, Minas Gerais and the club manager were interviewed and made several notes in relation to the traveling situation experienced by the club. For the organization and analysis, the data contained on the forms were tabulated using the SPSS for Windows, version 21. In the organization and analysis of qualitative data (the semi-structured interviews) was used content analysisproposed by Bardin. About fans Ipatinga, analyzed data point to a dissatisfaction with the output of the local club and an expectation of his return despite the mistrust generated by the club's immigration status. However, it remains an important brand of territorial belonging that the club has an instrument that strengthens these ties of affection. Since the data obtained in interviews with fans Betim, point to the creationof a link with the area where the club was installed and designed in the club the possibility of involvement and the early formation of an identification with the team through the moments Rest experienced especially on weekends. Now managers, evidence was found that an inefficient administration, in line with excessive reliance on public resources were the causes of the crisis that culminated the output ofIpatinga club. In Betim, the club has not reached the partnerships that craved with the public and private sector, generating a crisis that culminated in his return to Ipatinga.